Irregular urbanization as a catalyst for radical social mobilization: The case of the housing movements of S\~ao Paulo - Lucy Earle (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2011)
This study focuses on the city of S\~ao Paulo, Brazil and examines the ways in which irregular and illegal growth have influenced the collective action of social movements of the urban poor. The study describes how S\~ao Paulo grew as a socially segregated city during the twentieth century due to calculated neglect on the part of the municipal authorities. Highlighting the city's sociospatial inequality, degradation of the central districts and widespread irregularity, it illustrates how these factors have both negatively affected the urban poor and provided a catalyst for social mobilization.
Keywords: O1; O2; P2; R1; 330; urbanization; urban poor; inequality; social movements; Brazil